Correlations of religious beliefs with anxiety and depression of Chinese adolescents - Li, Lejun; Liu, Xiliang; Wang, Pingping; Qu, Miao; Xiu, Meihong (Frontiers in Psychiatry, 2024)
Objective This study was designed to investigate the prevalence of religious belief and its relationship with psychiatric symptoms among Chinese adolescents. Methods This study recruited 11,603 adolescents in Grades 7-9 from March 21 to 31, 2020 in five cities in China. The religious beliefs of adolescents were collected by asking whether they held religious beliefs and what type of religious beliefs they held. The Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 Scale (GAD-7) were used to assess depressive and anxiety symptoms in all adolescents. Demographics, religious beliefs, and mental health status were collected through the professional version of Wenjuanxing. Results Of 11,069 valid questionnaires collected, 847 (7.7%) reported holding religious beliefs. Adolescents with religious beliefs showed significantly more severe symptoms of depression and anxiety compared to those without religious beliefs (both p<0.05). Logistic regression analysis revealed that religious belief was a risk factor for symptoms of depression (OR = 1.37, 95%CI: 1.16-1.61, p < 0.001) and anxiety (OR = 1.49, 95%CI: 1.23-1.79, p < 0.001) after controlling age, gender, and parental marital status. Conclusions Our findings suggest that religiousness in adolescents was associated with a higher likelihood of depression/more intense depressive symptoms. In addition, religious Chinese adolescents should be provided with more resources to help them cope with mental health concerns.